ACADEMIC STRESS SCALE ON FINAL YEAR ENGLISH STUDENTS WHEN WRITING THESIS DURING PANDEMIC COVID-19 AT UNIVERSITAS MUHAMMADIYAH BENGKULU - Ivan Achmad Nurcholis; Washlurachim Safitri; Fitri Alfiani (JURNAL EDUSCIENCE, 2023)
Final year students are prone to stress, especially academic stress in thesis writing. This study aimed to find out the academic stress scale of final year English students at the Universitas Muhammadiyah Bengkulu (UMB) English Language Education Study Program in writing a thesis during the Covid-19 pandemic and to determine the most dominant academic stress scale among final year students at the English Language Education Study Program UMB in writing a thesis during the Covid-19 pandemic. In this study, researchers used descriptive quantitative research method to obtain data. The subjects of this study were even semester English students at UMB who were working on their thesis. The sample of this research was 57 students of the UMB English Education Study Program who were doing their thesis writing and guidance. The instruments used in this study were a Google form questionnaire and an interview guide. Questionnaire was used to obtain data about students' academic stress levels. There are two findings from this study, namely: (1) there are three academic stress scales for final year English students writing their thesis during a pandemic at UMB, namely; low stress scale (9.21%), moderate stress scale (32.46%), and high stress scale (58.33%); and (2) The most dominant academic stress scale for final year English students in writing their thesis during the Covid-19 pandemic was a high stress level. For final year students, they can reduce stress levels to avoid adverse effects on their mental and physical health such as asking for help from close friends or family to always support them during thesis writing. Keywords: academic Â stress scale; writing thesis; final year english studentsAbstrak Penelitian ini bertujuan untuk mengetahui skala stres akademik mahasiswa tingkat akhir Bahasa Inggris di Prodi Pendidikan Bahasa Inggris UMB dalam menulis skripsi di masa pandemi Covid-19 dan untuk mengetahui skala stres akademik yang paling dominan di kalangan mahasiswa tingkat akhir di Program Studi Pendidikan Bahasa Inggris. Prodi Pendidikan UMB dalam penulisan skripsi di masa pandemi Covid-19. Peneliti menggunakan metode penelitian deskriptif kuantitatif untuk memperoleh data. Subyek penelitian ini adalah mahasiswa bahasa Inggris semester genap Universitas Muhammadiyah Bengkulu yang sedang mengerjakan skripsi. Sampel penelitian ini adalah 57 mahasiswa Program Studi Pendidikan Bahasa Inggris UMB yang sedang mengerjakan skripsi dan bimbingan. Instrumen yang digunakan dalam penelitian ini adalah kuesioner Google form dan pedoman wawancara. Kuesioner digunakan untuk memperoleh data tentang tingkat stres akademik siswa. Ada dua temuan dari penelitian ini, yaitu: (1) ada tiga skala stres akademik untuk mahasiswa bahasa Inggris tingkat akhir yang menulis tesis mereka selama pandemi di UMB, yaitu; skala stres rendah (9,21%), skala stres sedang (32,46%), dan skala stres tinggi (58,33%); dan (2) Skala stres akademik mahasiswa tingkat akhir bahasa Inggris yang paling dominan dalam menulis skripsi selama pandemi Covid-19 adalah tingkat stres yang tinggi. Bagi mahasiswa tingkat akhir dapat mengurangi tingkat stres untuk menghindari dampak buruk bagi kesehatan mental dan fisik mereka seperti meminta bantuan teman dekat atau keluarga untuk selalu mendukung mereka selama penulisan skripsi.Kata Kunci: skala stres akademik; menulis tesis; siswa bahasa inggris tahun terakhir